PROYEK VIDEO SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN KREATIVITAS SISWA: A LITERATURE REVIEW - Uswatun Hasanah Hasanah; Dyan Evita Santi; Abdul Muhid (Jurnal Education and Development, 2022)
Technological advances have encouraged teachers to improve learning media to suit the new period so that students’ creativity can be further honed. This is because creativity is an indispensable skill for students to face an increasingly complex world. The purpose of this study is to demonstrate that video projects are a suitable medium for enhancing students' creativity. Therefore, this work relies on earlier research to get the necessary data.. The data used are accurate because they are obtained from journal articles, books, thesis, and seminar proceedings. In analyzing it, the authors then make a meta-analysis matrix from the data that has been collected. This paper shows the results that video project has proven to be able to enhance students’ ability to think creatively. They are encouraged to find creative ideas related to the theme of the video to be made. Their creativity will also be improved during the editing process to get interesting video results appropriate to their objective. Keywords: Creativity, Learning Media, Video Project, Literature Review